FORMULA DAN EVALUASI GEL PEMBERSIH TANGAN EKSTRAK BAWANG TIWAI (Eleutherine bulbosa (Mill.) Urb) - Yullia Sukawaty; Anita Apriliana; Husnul Warnida (Jurnal Ilmiah Manuntung, 2017)
Bawang tiwai (Eleutherine bulbosa (Mill.) Urb.) acts as an antibacterial because it contains a class of alkaloids, flavonoids, saponins, tannins, glycosides, triterpinoida / steroid, anthraquinone glycosides.Bawang tiwai onions can be used as an antibacterial active ingredient formulated in a gel hand sanitizer. The purpose of this study to determine the effect of varying concentrations of alcohol on the physical properties of gel preparation and inhibition of E.coli bacteria which are formulated in the form of a gel hand sanitizer bawang tiwai extract. Research conducted on fomula gel hand sanitizer bawang tiwai extract with various concentrations of alcohol F1 0%, F2 10%, F3 20%, F4 60% include (organoleptic, homogeneity, pH, dispersive power, consistency and viscosity) and continued with test inhibition of E. coli using disc diffusion method (Kirby-Bauer) in F1 0%, 10% F2, F3 20%, K (-) 60% and K (+) Triclosan 0.1%. Data were analyzed with SPSS 16.0 using Kruskal Wallis test with a level of 95%, α = 0.05. Gel hand sanitizer contains bawang tiwai extract 20% meets the requirements of the physical stability and have antibacterial inhibition of E. Coli